Assessment of the feasibility of the formulation of preparation for the growth inhibition of metronidazole-resistant strains isolated from the periodontal pockets - Toskić-Radojičić Marija; Nonković Zorka; Lončar Irma; Varjačić Milomir (Vojnosanitetski Pregled)
Introduction. Topical metronidazole benzoate preparations, applied directly into the space between the teeth and periodontal tissue, are the treatment of choice for periodontal pockets. Oleogels and hydrogels, as the biomucoadhesive bases for the manufacturing of these preparations, were developed in our previous trials. The aim of our latest research was to develop a preparation that would solve the problem of inhibiting the metronidazole-resistant anaerobic strains, isolated from the periodontal pockets. Methods. Metronidazole-resistant strains were isolated from the periodontal pocket swabs, using the established susceptibility testing. Further testing of the antimicrobial activity of the prepared formulations was performed by the membrane-free diffusion method in agar gel. Oleogels and hydrogels were tested with: tetracycline (2.5%), metronidazole (25%), and metronidazole benzoate (40%), as well as with oleogels and hydrogels containing the combination of 2.5% tetracycline and 40% metronidazole benzoate. Results. Satisfying results were achieved with the preparation containing 2.5% tetracycline along with metronidazole benzoate. The main fact revealed by this study was that there was no synergism in tetracycline and metronidazole benzoate activities, if the strain was susceptible to both active substances. Conclusion. The best results in the inhibition of the growth of metronidazole-resistant anaerobic strains were obtained by 2.5% tetracycline and metronidazole benzoate preparations in oleogel base.